Disruptive Innovation in Indian Aerospace and Defence Industry. (December 2020) - Rao, Shuktij Singh; Banik, Arindam; Khanna, Ashutosh; Philip, Deepu
This article analyses disruptive innovation in Indian aerospace and defence industry using a theoretical model developed on the basis of Christensen's framework for analysing disruptive innovation and by addressing the requirements of aerospace and defence industry. This framework is then used to collect data from key stakeholders and analyse the movements of Indian aerospace and defence industry. Analysis of a large sample of data reveals that there are forces of disruptive innovation that have been set in motion in the Indian aerospace and defence industry by recent events driven by the signals of changes in the industry and the steps taken by Government of India; however, they do not appear to be sufficient to be able to drive innovation and business activity that may amount to a scale of disruptive innovation due to lack of user participation and inadequate access to the global network of technology and management expertise. JEL Classifications: O31, O32, O33, O38